2019
DOI: 10.1128/jb.00581-18
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of hsdS Inversions in the cod Locus of Streptococcus pneumoniae

Abstract: Streptococcus pneumoniae(pneumococcus), a major human pathogen, is well known for its adaptation to various host environments. Multiple DNA inversions in the three DNA methyltransferasehsdSgenes (hsdSA,hsdSB, andhsdSC) of the colony opacity determinant (cod) locus generate extensive epigenetic and phenotypic diversity. However, it is unclear whether all threehsdSgenes are functional and how the inversions mechanistically occur. In this work, our transcriptional analysis revealed active expression ofhsdSAbut no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 58 publications
2
27
0
Order By: Relevance
“…Our previous study has found that the reversible switch between O and T colony phenotypes is controlled by the PsrA-catalyzed inversions of the three invertible regions in the cod locus [5,9] (Fig 2A). Therefore, enzymatic inactive psrA Y247A mutant (with a point mutation in the catalytic residue tyrosine 247) is locked in either O or T colony phase [9].…”
Section: Colony Phases Are Regulated By the Psra-dependent And -Indepmentioning
confidence: 92%
See 3 more Smart Citations
“…Our previous study has found that the reversible switch between O and T colony phenotypes is controlled by the PsrA-catalyzed inversions of the three invertible regions in the cod locus [5,9] (Fig 2A). Therefore, enzymatic inactive psrA Y247A mutant (with a point mutation in the catalytic residue tyrosine 247) is locked in either O or T colony phase [9].…”
Section: Colony Phases Are Regulated By the Psra-dependent And -Indepmentioning
confidence: 92%
“…Our previous study has found that the reversible switch between O and T colony phenotypes is controlled by the PsrA-catalyzed inversions of the three invertible regions in the cod locus [5,9] (Fig 2A). Therefore, enzymatic inactive psrA Y247A mutant (with a point mutation in the catalytic residue tyrosine 247) is locked in either O or T colony phase [9]. To determine whether the impact of RR06, RR08, RR09, RR11 and RR14 on phase variation requires PsrA-mediated inversions, we constructed deletion mutant in each of these genes in the O-locked psrA Y247A strain, which was previously shown to produce only the O colonies [5] ( Fig 2B; S2 Fig).…”
Section: Colony Phases Are Regulated By the Psra-dependent And -Indepmentioning
confidence: 92%
See 2 more Smart Citations
“…For example, sub‐components of the hsdS gene of the well‐characterised complex PV RM of Streptococcus pneumoniae , SpnIII, can exist in one of six possible orientations. Each of these unique TRD combinations is associated with a different DNA methylation pattern and some of them can impact on invasive disease potential in mice and the invasion‐associated opaque colony phenotype (Li et al, , ; Manso et al, ; Oliver, Roy, Kumar, Lefkowitz & Swords, ). The simplicity of these findings is challenged by variable experimental observations, suggesting that genetic background may influence links between methylation and colony opacity, and by the extensive hsdS allelic variation resulting in differing dominant methylation patterns among pneumococcal strains (De Ste Croix et al, ).…”
Section: Specific Hypermutable Mechanisms Found In Bacterial Pathogensmentioning
confidence: 99%